Sport in Literature: Sports Passion in the Literary Output of Krzysztof Zuchora on the Example of Selected Poems - Michał Mazurkiewicz (Jan Długosz University in Częstochowa, 2023)
Sport has been a source of artistic inspiration since antiquity, e.g. in ancient Greece the sporting heroes of that time were passionately sung about. This is also true of literature, which often depicts the drama of sporting rivalry and describes the resulting strong emotions; not once does it evoke nostalgia for times gone by, for important sporting events that are constantly recalled. This article analyzes the presence of sport (using the example of sports disciplines and prominent figures) in poetry through the works of a contemporary Polish author, Krzysztof Zuchora (born in 1940). The research carried out required familiarization with numerous monographs and other publications (academic articles, popular science articles and chapters in monographs), both in English and Polish, in which the broadly understood relationship between sport and literature is presented; the primary source material, however, consists mainly of selected poetic works by the above-mentioned outstanding author. Importantly, the interpretation of several characteristic sports poems by Krzysztof Zuchora was combined with the analysis of historical sources. The study has undeniably shown that literary works are an important chronicle of historical events, while sport - as a powerful source of inspiration par excellence - has great potential for shaping human attitudes and building a better world in many respects.